2020
DOI: 10.7592/ejhr2019.7.4.dionigi
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive persons, caregiving strategies and humour: the case of Italian and Israeli medical clowns

Abstract: The medical clown is a healthcare practitioner whose character is strictly associated with the performer’s own personality. In this study, the relationships between level of sensory processing sensitivity (SPS), caregiving strategies and humour in Italian and Israeli clowns were compared. Participants were 159 medical clowns (97 Italian and 62 Israeli), ranging from 22 to 74 years of age, who completed a demographic questionnaire, the self-reported Highly Sensitive Person Scale, the Caregiving Strategies Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The common knowledge is that MCs focus on humor with the ultimate goal of making the patient smile ( Battrick et al, 2007 ; Dionigi & Goldberg, 2019 ; Finlay et al, 2014 ; Friedler et al, 2017 ; Mora-Ripoll, 2010 ). However, this study showed that expressions of joy and relief were considered positive but were not the only or even the principal goal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The common knowledge is that MCs focus on humor with the ultimate goal of making the patient smile ( Battrick et al, 2007 ; Dionigi & Goldberg, 2019 ; Finlay et al, 2014 ; Friedler et al, 2017 ; Mora-Ripoll, 2010 ). However, this study showed that expressions of joy and relief were considered positive but were not the only or even the principal goal.…”
Section: Discussionmentioning
confidence: 99%
“…Medical clowns (MCs), also called hospital clowns or clown doctors, are trained professionals who aim to change the perception of the hospital environment by creating humoristic situations to elicit laughter and joy in children’s wards as well as with adults and older adults ( Dionigi et al, 2014 ; Dionigi & Goldberg, 2019 ; Friedler et al., 2017 ; Koller & Gryski, 2008 ; Lalantika & Yuvaraj, 2020 ; Linge, 2008 ; Ofir et al, 2016 ; Weaver et al, 2007 ). In many cases, patients, families, and staff value MCs ( Dionigi & Canestrari, 2016 ; Higueras et al, 2006 ; Schwebke & Gryski, 2003 ; Warren & Spitzer, 2013 ), especially for improving patients’ physical and mental well-being through creating an alternative atmosphere ( Dionigi et al, 2014 ; Friedler et al, 2017 ; Lopes-Júnior et al, 2020 ; Nuttman-Shwartz et al, 2010 ; Weaver et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the emergence of hospital clowns in North America in the 1980s, it has become a popular practice in paediatric settings, mainly in acute and rehabilitation hospitals worldwide 14. Hospital clowns have a positive effect on paediatric patient outcomes, mainly in patients with acute conditions and during medical procedures 14151617181920. Hospital clowns are also increasingly thought to have a complementary role in healthcare by easing the recovery of these patients 1415…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have stressed the risk of emotional exhaustion for clown therapists and the need to have appropriate coping strategies to compensate for their vulnerabilities [ 57 ]. Dionigi had shown that the best predictor to keep in mind for emotional exhaustion in clown therapists was the neuroticism trait [ 58 ]. Some have suggested it can limit the risk of emotional exhaustion, by learning to keep the role being played separate from one’s own person [ 59 , 60 , 61 ], while others recommend a number of expedients that can be applied to mitigate the risk of burnout: spacing out vacations, frequently consulting with a supervisor, and relying on consultation with a mental health professional in the event of perceived discomfort [ 62 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%